THE EFFECTIVENESS OF AUDIOVISUAL MEDIA IN ISLAMIC RELIGIOUS EDUCATION (PAI) LEARNING AT SD NEGERI 2 BUNGTIANG - Baiq Murdini (Formad English Foundation NTB-Jakarta, 2024)
The study explores the effectiveness of audiovisual media in enhancing students' learning outcomes in Islamic Religious Education (PAI) at SD Negeri 2 Bungtiang. The primary aim was to assess whether audiovisual tools improve student engagement, comprehension, and retention in PAI lessons. A quasi-experimental design was used, with an experimental group (16 students) receiving audiovisual-based instruction and a control group (15 students) receiving traditional teaching. The results show a significant improvement in the posttest scores of the experimental group (mean = 78.58), while the control group demonstrated modest gains (mean = 59.45). The study concludes that audiovisual media significantly enhances learning outcomes by improving student engagement and comprehension. The research recommends the integration of diverse audiovisual content, investment in technological tools, and teacher training to optimize learning. These findings contribute to the advancement of Islamic education by promoting innovative teaching strategies. Future research could explore the long-term impacts of audiovisual media and its effectiveness across different educational contexts.